2018
DOI: 10.1080/15389588.2018.1498089
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of wearing a bicycle helmet for impacts against the front of a vehicle and the road surface

Abstract: Wearing a helmet reduces skull fracture risk when the frontal and lateral parts of the helmet impact vehicle parts (excluding the hood) at 35 km/h and the road surface at 20 km/h. However, when the lateral part of the helmet impacts the B-pillar, the helmet cannot effectively reduce the skull fracture risk at these real-world velocities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…The 10 m/s velocity of impact was based on previous studies in which bicycle accidents were shown to be common causes for dental trauma . The 10 m/s impact velocity simulates a patient involved in a bicycle collision, accident or fall …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 10 m/s velocity of impact was based on previous studies in which bicycle accidents were shown to be common causes for dental trauma . The 10 m/s impact velocity simulates a patient involved in a bicycle collision, accident or fall …”
Section: Discussionmentioning
confidence: 99%
“…28,29 The 10 m/s impact velocity simulates a patient involved in a bicycle collision, accident or fall. 30 In this study, a 100N functional biting load was simulated for comparison with the 10 m/s impact model. This anterior bite force was based on values from two studies which were found to vary between 59.5 and 155 N. 14,31 When the bite load was applied on the palatal surfaces of the incisors, the stresses around the adjacent teeth were about 75% lower than during the impact.…”
Section: Discussionmentioning
confidence: 99%
“…[34][35][36][37] Previous studies reveal a discrepancy between bikers acknowledging the importance of helmet use versus actually choosing to wear helmets, which indicates that helmet advocacy initiatives might improve rates of helmet use. 38,39 In conjunction with interventions such as improving bike lanes and educating motorists, helmet advocacy may help to reduce the incidence of cycling-related TSIs.…”
Section: Discussionmentioning
confidence: 99%
“…Everyone must use protective equipment when riding a bicycle to minimize this risk of death and injury. 7 Since bicycle helmet, which is a protective equipment, significantly reduces face, nose fractures and fractures around eye and brain injuries, its use need to be promoted and popularized. [7][8][9] Despite such protection provided by helmets, most bicyclists do not wear helmets at all.…”
mentioning
confidence: 99%
“…7 Since bicycle helmet, which is a protective equipment, significantly reduces face, nose fractures and fractures around eye and brain injuries, its use need to be promoted and popularized. [7][8][9] Despite such protection provided by helmets, most bicyclists do not wear helmets at all. The study performed by Kılınç on adolescents observed that only 7.6% of them wore bicycle helmets.…”
mentioning
confidence: 99%